Potential Reserviours Of Whitefly Transmitted Begomo Virus Causing Leaf Curl Disease In Chilli (Applied Biological Research, 2016)
A total of 19 weeds viz., Abutulon theopharasti, Achyranthus aspara,  Ageratum conizoides, Cyperus esculentus, Malvestrum coromandelianum,  Amaranthus viridis, Boerhavia diffusa, Calotropisgigantean, Cannabis  sativa, Commelina benghalensis, Digera arvensis, Eclipta alba, Euphorbia  hirta, Tinospora cordifolia, Ipomoea pestigridis, Parthenium  hysterophorus, Phylanthus niruri, Physalis minima and Tribulus  errestris, belonging to 12 families, were collected from chilli (Capsicum  annum) fields in Punjab (India) with the aim to find out alternate hosts  of Begomoviruses affecting drastically chilli crop. Of these, Eclipta alba,  Ageratum conizoides, Amaranthus viridis, Ipomoea pestigridis, Abutulon  theopharasti, Cannabis sativa and Commelina benghalensis showed  typical leaf curl symptoms with vein clearing as predominant symptom  exhibited by the above symptomatic weed species. Rest weeds did not possess any symptom. All the weed species were subjected to PCR and  only Commelina benghalensis was found positive for Begomovirus with  expected fragment size of ~575 bp of core protein region. Further,  rolling circle amplification (RCA) technique was adopted to develop  concatemer of circular DNA of virus. The RCA product when used as  template in PCR showed amplification (~575 bp) for all the symptomatic  and asymptomatic weed species, except Calotropis gigantean. The phylogenitic analysis revealed the presence of chilli leaf curl India virus,  tomato leaf curl Jodepur virus and papaya leaf crumple virus in weed  samples. Perusal of literature revealed that Commelina benghalensis  aspara, Boerhavia diffuda, Cyperus esculentus, Tinospora cordifolia and Ipomoea pestigridis have not so far been reported as hosts of  Begomoviruses, so this is the first report in this direction.
Keywords: Begomovirus; chilli; leaf curl; whitefly; weed hosts